Preliminary results about the relationship between fat content and fatty acid composition of some meat parts of beef - Szokol, Balázs; Éva, Vargáné Visi (Acta Agraria Kaposváriensis, 2022)
This work aimed to investigate whether the lipid profile differs among beef cuts purchased from retail stores. Fat content, fatty acid composition, and conjugated linoleic acid content of different cuts were determined. Moreover, the relationship between the fat content and fatty acid composition was evaluated to see whether the change in the fat content of beef affects the fatty acid composition of beef lipids. During five weeks, the thick flank, fore rib, thick rib, and neck samples were obtained at a local store. In addition, conjugated linoleic acid content and fatty acid composition were measured with a gas chromatograph equipped with a flame ionization detector (GC-FID) after transesterification of acyl lipids in the form of fatty acid methyl esters (FAME). There were only a few significant differences among beef cuts. Regarding the measured nutrients, the ratio of arachidonic acid and monounsaturated fatty acids (MUFA) within lipids differed among cuts. In contrast, the ratio of the other fatty acids and the conjugated linoleic acid content were not affected by the type of cut. Nevertheless, when the pulled data were analysed, irrespectively of the cuts, it was found that the more fat in the beef was, the less healthy the lipid profile became. The fat content had a significant positive correlation (r=0.663, P=0.001) with the ratio of saturated fatty acids (SFA) and a significant negative relationship (r=-0.621, P=0.004) with the ratio of polyunsaturated fatty acids (PUFA) within beef lipids. Consequently, enhanced fat deposition can impair the quality of meat not only with the higher fat and less lean meat content of carcasses but also can compromise the fatty acid profile, causing a significantly more saturated character. This tendency could be seen clearly, although this preliminary research used only a limited number of samples.